Epicardial adipose tissue (EAT) volume is related to subclinical atherosclerosis and major adverse cardiovascular events (MACE) in asymptomatic subjects. (14th October 2021) - Sousa, A; Mendonca, M I; Santos, M; Temtem, M; Mendonca, F; Sousa, A C; Rodrigues, M; Freitas, S; Henriques, E; Borges, S; Guerra, G; Drumond, A; et al.
Abstract: Introduction: Epicardial adipose tissue (EAT) is an emerging cardiovascular risk marker. It has been suggested to be an inflammatory mediator with a role in subclinical atherosclerosis and coronary artery disease. However, its prognostic relevance in hard clinical outcomes remains thoroughly unexplored in the literature. Purpose: Evaluate the prognostic relevance of EAT, regarding the occurrence of major adverse cardiovascular events (MACE) in an asymptomatic population. Methods: 895 asymptomatic volunteers were prospectively enrolled in a single Portuguese center (mean age 51.9±7.7, 78.5% male) and underwent a median follow-up time of 3.7 years (IQR 5.0). EAT volume was measured by Cardiac Computed Tomography (CCT) using a modified simplified method. Participants were distributed into two groups, above and below the EAT-volume median. We compared both groups regarding the occurrence of MACE through univariate analysis, Kaplan-Meier Survival curves and log-rank test. Association to subclinical atherosclerosis was addressed using correlation between EAT volume and calcium score (Agatson). Results: There is a strong correlation between EAT volume and calcium score (r=0.205, p<0.0001), sustaining that it may play an important role in mediating coronary artery disease and subclinical atherosclerosis. Patients with higher EAT volume, were exposed to higher occurrence of MACE on follow-up [70.4% (19 of 27) vs 49.4% (429 of 868), p=0.032] with a clearer separation of the curves after 5.7 years. Conclusion: In an asymptomatic population, EAT volume seems to be related to subclinical atherosclerosis and to the occurrence of adverse cardiovascular events on long-term follow-up. Our study addresses some unanswered questions, such as the prognostic relevance of EAT as an emerging cardiovascular risk marker. FUNDunding Acknowledgement: Type of funding sources: None.